Effects of Systemic Lidocaine on Postoperative Recovery Quality and Immune Function in Patients Undergoing Laparoscopic Radical Gastrectomy - Lv X; Li X; Guo K; Li T; Yang Y; Lu W; Wang S; Liu S (Dove Medical Press, 2021)
Xueli Lv,1,* Xiaoxiao Li,1,* Kedi Guo,1,* Tong Li,1 Yuping Yang,1 Wensi Lu,1 Shuting Wang,1 Su Liu1,2 1Jiangsu Province Key Laboratory of Anesthesiology, Xuzhou Medical University, Xuzhou, Jiangsu, People’s Republic of China; 2Department of Anesthesiology, The Affiliated Hospital of Xuzhou Medical University, Xuzhou Medical University, Xuzhou, Jiangsu, People’s Republic of China*These authors contributed equally to this workCorrespondence: Su LiuDepartment of Anesthesiology, The Affiliated Hospital of Xuzhou Medical University, Xuzhou Medical University, Xuzhou, Jiangsu, 221000, People’s Republic of ChinaTel +86 18118309692Fax +0516-8346-9496Email 150040009@qq.comObjective: This study aimed to explore the effects of lidocaine on postoperative quality of recovery (QoR) and immune function in patients undergoing laparoscopic radical gastrectomy.Methods: In total, 135 patients were enrolled and were equally randomized to receive low-dose lidocaine (Group LL: 1.5 mg/kg bolus followed by an infusion at 1.0 mg/kg/hour) or high-dose lidocaine (Group HL: 1.5 mg/kg bolus followed by an infusion at 2.0 mg/kg/hour) or Controls (Group C: received a volume-matched normal saline at the same rate). The primary outcome was a QoR-40 score on postoperative day (POD) 1. Secondary outcomes were a QoR-40 score on POD 3, levels of inflammatory factors (IL-6, IL-10, TNF-α) and CD4+T cells, CD8+T cells proportions, and CD4+/CD8+ cell ratios and postoperative recovery of bowel function.Results: There were no statistically significant differences in patient characteristics at baseline. The total QoR-40 scores on POD 1 in Group HL (171.4± 3.89) were higher than those in Group LL (166.20± 4.05) and in Group C (163.40± 4.38) (adjusted P< 0.001). Differences in the dimension scores of QoR-40 for pain, physical comfort, and emotional state were significant across the three groups. Lidocaine administration significantly reduced the release of IL-6, IL-10, TNF-α, and attenuated immune changes induced by trauma. Kaplan–Meier curves showed that the median time to the first exhaust and defecation were shorter in the Group HL than in Groups LL and C (1.55 days vs 2.4 days vs 2.6 days, log rank P< 0.0001; and 2.86 days vs 3.22 days vs 3.46 days, log rank P=0.002, respectively). Additionally, patients in lidocaine groups required less remifentanil consumption and experienced lower pain intensity, compared with the control group.Conclusion: Systemic lidocaine improved postoperative recovery, alleviated inflammation and immunosuppression, and accelerated the return of bowel function, and is thus, worthy of clinical application.Clinical Trials Registration: ChiCTR2000028934.Keywords: lidocaine, QoR-40, postoperative quality of life, radical gastrectomy